KERACUNAN BESI PADA TANAMAN PADI DAN UPAYA PENGELOLAANNYA PADA LAHAN SAWAH - Syafruddin, Syafruddin (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
As a staple food of people in Indonesia, rice reserve must be met sufficiently. The effort to fulfill demand of rice has drawn attention to intensification, extensification as well as diversification programs. Extensification has only possible been carried out in acid soils, having relative low nutrient status, high Fe, Al and Mn saturations. Iron toxicity is one of primary limiting factors to obtain high yielding production in acid soils such as inceptisol and ultisol. Iron toxicity may highly reduce the yield harvested up to 90 %. To correct the low productivity level of acid soil for rice, it is important to apply appropriate technology considerable to soil and indigenous farmer requerements. Some procedures have been practically used to increase the productivity of acid soil and reduce the symptoms of iron toxicity i.e. improvement of rice varieties tolerant to high iron status, application of fertilization in proportional balance in order to overcome negative effects of iron toxicity, otherwise combinations of better control of watering system with providing aerob condition by turns, as wel as appropriate and sustainable use of organic matter.